The effects of extrasynaptic substance P on nociceptive neurons in laminae I and II in rat lumbar spinal dorsal horn - Liu, Xianguo; Sandkühler, Jürgen (Neuroscience, 1995)
Inflammation of the skin induces release and extrasynaptic spread of neuropeptides such as substance P mainly in spinal laminae I and II and causes changes in discharge properties of nociceptive neurons in spinal dorsal horn. To evaluate the role of extrasynaptic substance P we have superfused the spinal cord at recording segment with artificial cerebrospinal fluid or with substance P. A total of 102 multireceptive neurons responding to both noxious and innocuous skin stimulation were recorded in laminae I or II of lumbar spinal dorsal horn in pentobarbital anaesthetized rats. During superfusion with substance P (10 or 100 μM) significant increases of background activities (from 2.2 ± 0.6 to 8.4 ± 3.2 imp./s, mean ± S.E.M.), enlargement of cutaneous receptive fields (from 359.9 ± 60.4 to 465.5 ± 77.3 mm2) and enhanced responses to mechanical (from 89.1 ± 22.7 to 147.0 ± 27.5 imp./5 s) but not thermal noxious skin stimuli were observed in the 22 neurons tested. Noxious heat-evoked responses and C-fibre-evoked responses were changed in both directions. In 50 other neurons, the coefficients of dispersion of interspike intervals, which is an indicator of burst-like discharges, were significantly reduced (from 60.4 ± 5.5 to 52.7 ± 5.3) after application of substance P. Substance P induced oscillations in background activities in 13 of 40 non-rhythmic neurons and depressed oscillations in 2 of 11 neurons. Cross-correlations of discharges of pairs simultaneously recorded neurons were flat (n = 4), or had a central peak (n = 19) or a central trough (n = 2) and were not changed qualitatively by extrasynaptic substance P. Thus, extrasynaptic substance P can modify not only discharge rates but also discharge patterns in the spinal dorsal horn.
Online 6 April 2000
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.05.2021